Mitophagy in hepatic ischemia-reperfusion injury - ZHANG Xiangxin, LI Wen (Jichu yixue yu linchuang, 2024)
In case of hepatic ischemia-reperfusion injury (HIRI), mitophagy is induced by multiple pathways such as PINK1/Parkin and mitophagy receptor, which is closely related to mitochondrial dynamic related protein. Mitophagy is a double-edged sword. Moderate mitophagy is effective in reducing the oxidative stress and maintaining mitochondria homeostasis, thereby reducing hepatocyte apoptosis and necrosis, inhibiting inflammation response and mitigating HIRI. However excessive mitophagy will aggravate HIRI. So research on the role and mechanism of mitophagy may facilitate the development of new strategy for prevention and clinical treatment of HIRI.